Pengaruh Pemberian Nutrisi Daun dan Jenis Pupuk terhadap Pertumbuhan dan Hasil Tanaman Cabai Merah Besar (Capsicum annum L.) - Turmuktini, Tien; Aisyah, Iis; Simarmata, Tualar; Oktav Fauziah, Nicky; Putrian Syah, Anita (Paspalum: Jurnal Ilmiah Pertanian, 2024)
The research was carried out in an experimental garden at the Faculty of Agriculture, Padjadjaran University, Jatinagor District, Sumedang Regency. The altitude of the place is 700 meters above sea level. This research was conducted from May to August 2022. The purpose of this study is to determine the interaction of foliar nutrition and fertilizer type on the growth and yield of large red chili plants (Capsicum annum L). The environmental design of this research is a Split Plot Design which consists of two treatments and is repeated four times. The main plot is the administration of a foliar nutrient solution (F) consisting of two levels: f0 (without administration) and f1 (one-time 10-day administration). The plot is a type of fertilizer (P) consisting of three levels: p1 cow manure 4 t ha-1 p2, Soil Conditioner Growth Booster (SCGB) 6 kg ha-1 and p3 ameliorant plus 4 t ha-1. The data were analyzed using Analysis of Variance with Duncan's double-spacing advanced test at a rate of 5%. The results showed that there was an interaction with growth (Plant height 1 Week After Planting (WAP), 2 WAP, 3 WAP, Number of leaves 3 WAP, stem diameter 2 WAP, 3 WAP, 4 WAP, 5 WAP) and yield (Weight per fruit). The best results were shown in foliar nutrition and SCGB administration against plant height growth of 2 WAP, 3 WAP, leaf count of 3 WAP and stem diameter of 3 WAP as well as foliar nutrition and ameliorant plus feeding of 5 WAP stem diameter. Types of ameliorant plus fertilizers that were not fed foliar nutrition show the best results against plant height growth of 1 WAP stem diameter of 2 WAP, 4 WAP and weight yield per fruit.